Increased vulnerability to COVID‐19 in chronic kidney disease - Carlson, N. (J Intern Med, 2021)
BACKGROUND: The significance of chronic kidney disease on susceptibility to COVID‐19 and subsequent outcomes remains unaddressed. OBJECTIVE: To investigate the association of estimated glomerular filtration rate (eGFR) on risk of contracting COVID‐19 and subsequent adverse outcomes. METHODS: Rates of hospital‐diagnosed COVID‐19 were compared across strata of eGFR based on conditional logistic regression using a nested case–control framework with 1:4 matching of patients diagnosed with COVID‐19 with controls from the Danish general population on age, gender, diabetes and hypertension. Risk of subsequent severe COVID‐19 or death was assessed in a cohort study with comparisons across strata of eGFR based on adjusted Cox regression models with G‐computation of results to determine 60‐day risk standardized to the distribution of risk factors in the sample. RESULTS: Estimated glomerular filtration rate was inversely associated with rate of hospital‐diagnosed COVID‐19: eGFR 61–90 mL/min/1.73m(2) HR 1.13 (95% CI 1.03–1.25), P = 0.011; eGFR 46–60 mL/min/1.73m(2)  HR 1.26 (95% CI 1.06–1.50), P = 0.008; eGFR 31–45 mL/min/1.73m(2) HR 1.68 (95% CI 1.34–2.11), P < 0.001; and eGFR ≤ 30 mL/min/1.73m(2) 3.33 (95% CI 2.50–4.42), P < 0.001 (eGFR > 90 mL/min/1.73m(2) as reference), and renal impairment was associated with progressive increase in standardized 60‐day risk of death or severe COVID‐19; eGFR > 90 mL/min/1.73m(2) 13.9% (95% CI 9.7–15.0); eGFR 90–61 mL/min/1.73m(2) 16.1% (95% CI 14.5–17.7); eGFR 46–60 mL/min/1.73m(2) 17.8% (95% CI 14.7–21.2); eGFR 31–45 mL/min/1.73m(2) 22.6% (95% CI 18.2–26.2); and eGFR ≤ 30 mL/min/1.73m(2) 23.6% (95% CI 18.1–29.1). CONCLUSIONS: Renal insufficiency was associated with progressive increase in both rate of hospital‐diagnosed COVID‐19 and subsequent risk of adverse outcomes. Results underscore a possible vulnerability associated with impaired renal function in relation to COVID‐19.